The role of men in contraceptive use and fertility preference in Hossana Town, southern Ethiopia - Tuloro, Tsedeke; Deressa, Wakgari; Ali, Ahmed; Davey, Gail (The Ethiopian Journal of Health Development, 2016)
Abstract Background: Family planning programs have always been considered as the interventions of choice for slowing population growth. These programs, however, are seen to give relatively little attention to the roles that could be played by men regarding fertility regulation. Consequently, there is a shortage of information on family planning knowledge, attitudes and practices among married men, and their fertility preferences in Ethiopia. Objective: The objective of this study hence, was to assess the role of men in contraceptive use and fertility preference among currently married men. Methods: The study used a community-based cross-sectional survey conducted from December 2003 to January 2004 in Hossana town, southern Ethiopia. A total of 773 currently married men in the age group of 20-64 years were included in the study. A total of nine Kebeles were selected from 15 Kebeles of the town using simple random sampling method. Study households were selected from each Kebele through systematic random sampling. Pre-tested, structured questionnaires were used for data collection. Results: The average number of living children per man was 3.8. The majority of the study participants (60.3%) reported wanting more children. About 91% of the respondents were familiar with at least one of the family planning methods. The most commonly known methods of family planning included the pill (79.4%), injection (78.5%), male condom (65.6%), Norplant (42%), and IUD (30.5%). Nearly half (48%) reported current use of contraceptives by their wives. An additional 15% had used a method some time in the past. Injection was the most commonly used method (58%), followed by the pill (27.5%). The main reasons for not using contraceptives included a desire to have more children (32%), opposition from the respondents (husband opposition) (23.2%), and fear of side effects (15%). About 90% of them approved the use of family planning methods, and two-thirds (66%) of the respondents had discussed about family planning matters with their wives during the last one year. More than half (54%) of the respondents reported joint decision-making on ’when to have another child’, and 80.9% reported agreement between spouses on a decision ’when to use contraceptives’. Conclusions: This study found high prevalence of knowledge of contraceptive methods among married men, but a relatively low utilization rate. Discussion between spouses and their joint decision-making on contraceptive use was also found to be high. Thus, family planning programs should not focus only on women, but they should also address men. Information, education and communication programs for promoting family planning methods should, thus, be strengthened. [Ethiop.J.Health Dev. 2006;20(3):152-15